Legal Annotation of Court Decision Number 75 / Pdt.Sus – Ipr / Merek / 2022 / Pn Niaga Jkt.Pst in Administrative Certainty for Famous Brands in Indonesia - Citraresmi Widoretno Putri; Suherman; Yuliana Yuli W; Beniharmoni Harefa; Satino (Jurnal Multidisiplin Madani, 2023)
Review of the trademark determination in court decision Number 75/Pdt.Sus-Hki/Merek/ 2022/Pn Niaga Jkt.Pst rejection of the application for the trademark GENHALILINTAR + Painting by Anofial Asmid because it was registered by PT SOKA CIPTA NIAGA on October 23 2017 with a Notification of Rejection Registration of the Mark "GENHALILINTAR + Painting" Agenda Number D002018027834 dated 31 December 2019 by the Directorate General of Intellectual Property and Decision of the Mark Appeal Commission / Defendant Number 375 / KBM / IPR / 2020 dated 8 September 2020. This turns out to be interesting because in Halilintar Anofial Asmid has registered the GENHALILINTAR + Painting brand in several classes, which of course contradicts the arguments in the Notice of Rejection and Decision of the Mark Appeal Commission. This paper uses normative legal research methods. With the conclusion Based on the legal annotation of the Decision that there are problems that occur in granting well-known trademark rights to certain people or civil legal entities, especially if the trademark holder is not the initial initiator of its popularity. In terms of administrative certainty of the GENHALILINTAR + Painting mark, state administrative legal action in trademark disputes can be filed against the decision to delete a registered mark at the initiative of the Minister. If there has not been an administrative Judge's Decision, the first principle is that the registered mark has a stronger position compared to the popular indication of a mark